Behind the hyperreality experience: the 2008 Beijing olympics opening ceremony - Ho, KT (New Zealand Asian Studies Society, 2011)
Some observers, such as Brooks (2008, August 12) in Harmony and the Dream, have considered collectivism as the key contribution to the aesthetics of the Opening Ceremony of the Beijing Olympics. Against such views, this paper takes the position that simulacra (Baudrillard, 1994, p. 125) of classical Chinese philosophy are presented as the core underpinning aesthetics of the Opening in a contemporary context, through the Western experience of hyperreality by means of digital technology, and supported by the collective aesthetics. The paper is based on research into the ‘behind-the-scenes’ documentary produced and broadcast by China Central Television (CCTV), and discourse about the Opening in the context of broader Internet discussions. Current discourses on collectivism in the aesthetics of the Opening have been associated with social and political concerns, rather than the art and design aesthetic paradigm that influences current consumer culture. However, it is not the intention of this paper to discuss the political references involved. The paper investigates that the contemporary reshaped classical Chinese philosophical aesthetics is the stimulus of the seemingly collective aesthetics at work. Such aesthetics is designed and presented to fulfill the expectation of the Western (or global) context; as such it is a copy of a copy of the Western constructed Chinese aesthetics that is at work. Though the behind-the-scenes documentary of CCTV is generally considered a marketing tool for the event, it provides useful data for investigation of the creative constituent of the hyperreal experience of the audience.